2004
DOI: 10.1021/ie0498394
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Heat Pretreatment of Li3N on Its H2 Storage Performance

Abstract: A comparison between the hydrogen storage performances of untreated and heat-treated Li3N was carried out using a volumetric method, temperature-programmed hydrogenation (TPH), and scanning electron microscopy (SEM). It was found that, during the first hydrogenation, the untreated Li3N could absorb fast (3 min), 5.5 wt % of hydrogen at 230 °C, and that 3200 min was needed to absorb an additional 2.5 wt % of H2. In contrast, the Li3N preheated at 400 °C in a vacuum for 4.5 h absorbed only 3 wt % in 3 min at 230… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…Since in Chen et al's report [1], the Li-N-H compound has been paid much attention for one of the new hydrogen storage systems [2][3][4][5][6][7][8][9][10][11]. Lithium nitride absorbs and desorbs a large amount of hydrogen in the two consecutive reactions as follows: Li 3 N + 2H 2 ↔ Li 2 NH + LiH + H 2 ↔ LiNH 2 + 2LiH.…”
Section: Introductionmentioning
confidence: 99%
“…Since in Chen et al's report [1], the Li-N-H compound has been paid much attention for one of the new hydrogen storage systems [2][3][4][5][6][7][8][9][10][11]. Lithium nitride absorbs and desorbs a large amount of hydrogen in the two consecutive reactions as follows: Li 3 N + 2H 2 ↔ Li 2 NH + LiH + H 2 ↔ LiNH 2 + 2LiH.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, many related studies have been reported all over the world [2][3][4][5][6][7][8][9][10][11][12][13][14]. Ichikawa (1) They claimed that the above dehydrogenation reaction is not a direct molecule-molecule reaction between LiNH 2 and LiH, but it can be expressed by an ammonia mediating model [7,15].…”
Section: Introductionmentioning
confidence: 99%
“…Since the hydrogen storage (H-storage) properties of the Li-N-H system was reported by Chen et al [1] as a new family of promising hydrogen storage materials, many relevant studies have been performed to understand and improve their H-storage properties all over the world [2][3][4][5][6][7][8][9][10][11][12][13]. As a result of those investigations, similar hydrogen storage systems i.e.…”
Section: Introductionmentioning
confidence: 99%